Pengembangan Media Pembelajaran Interaktif Berbasis Web Menggunakan Google Slides pada Mata Pelajaran Informatika Kelas XB MA Al Fattahiyyah - Fida Khusna Anggraini; Bian Dwi Pamungkas (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to develop interactive web-based learning media using Google Slides for Grade X Informatics at MA Al Fattahiyyah. The research addresses students’ low interest and understanding of Informatics, largely due to unengaging teaching methods and limited use of visual and interactive media. To meet the demands of 21st-century education, technology integration in learning is essential to improve both effectiveness and student engagement. The study employs the DDDE (Decide, Design, Develop, Evaluate) development model, which involves four core stages. The final product presents the topic “Social Impact of Informatics” in a structured, visual, and interactive format via Google Slides. It features animations, quizzes, intuitive navigation, and collaborative elements that are accessible on multiple devices. Validation results show the media is highly feasible for classroom use, achieving scores of 88.9% from media experts, 92.72% from material experts, and 85.33% and 83.44% from small and large group trials. These findings indicate that the media effectively improves students’ comprehension and learning motivation. In conclusion, this Google Slide-based media provides an innovative and practical solution to enhance Informatics learning in senior high school settings.